2017
DOI: 10.3390/su9030374
|View full text |Cite
|
Sign up to set email alerts
|

Forest Fragmentation and Driving Forces in Yingkou, Northeastern China

Abstract: Forest fragmentation, the process of changing original large and intact forest patches into smaller and isolated areas, significantly influences the balance of surface physical environment, biodiversity, and species richness. Sufficient knowledge of forest fragmentation is necessary to maintain ecological balance and promote sustainable resource utilization. This study combines remote sensing, geographical information systems, and landscape metrics to assess forest fragmentation at landscape and pixel levels d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This study outcome suggests that the forest patches would likely be larger in an area far away from the access roads as compared to patches that are closer to the access roads. In a similar study in northeastern China [ 39 ], it was found that forest patches that are closer to roads (highways) are more likely to be smaller as compared to the patches that are far away from the roads. Moreover, the outcome of our study corroborates a related study from tropical forest environments (Indonesia, Gabon, Democratic Republic of Congo, Republic of Congo, Suriname, and Mexico) which shows that more forests are left intact in areas farther from roads away as compared to forest patches that are within proximity to roads [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study outcome suggests that the forest patches would likely be larger in an area far away from the access roads as compared to patches that are closer to the access roads. In a similar study in northeastern China [ 39 ], it was found that forest patches that are closer to roads (highways) are more likely to be smaller as compared to the patches that are far away from the roads. Moreover, the outcome of our study corroborates a related study from tropical forest environments (Indonesia, Gabon, Democratic Republic of Congo, Republic of Congo, Suriname, and Mexico) which shows that more forests are left intact in areas farther from roads away as compared to forest patches that are within proximity to roads [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we present methods from geographic information systems (GIS), remote sensing and statistics to process geospatial data and show the relationship between land uses and forest cover patches. A similar approach has been used successfully in a study to model forest fragmentation, land use and other factors in northeastern China [ 39 ]. This study presents important information that reflects environmental, social and economic conditions and directly informs forest policies and management plans about the need to protect forest resources and ensure sustainable land uses in and around protected landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…The region covers 527,500 ha, and mountainous areas account for approximately 50% of the area. Benefiting from these topographic and geography features, the area has abundant forest and wetland resources, making up about 46% and 6% of the total area, respectively [41]. Over the past 15 years, the region has undergone remarkably rapid economic growth and urbanization, and a considerable decrease in forest land and wetlands [41].…”
Section: Study Area and Data Processingmentioning
confidence: 99%
“…Benefiting from these topographic and geography features, the area has abundant forest and wetland resources, making up about 46% and 6% of the total area, respectively [41]. Over the past 15 years, the region has undergone remarkably rapid economic growth and urbanization, and a considerable decrease in forest land and wetlands [41]. Therefore, the natural resources should be analyzed and monitored in Yingkou, to protect natural environment and ecosystem processes.…”
Section: Study Area and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation